How do Gender Studies Contribute to the Field of Literary Studies? - Luque, Cecilia Inés (Revista Melibea, 2024)
I give here a possible answer, without pretending to be exhaustive, based on my own academic experience with feminist literary studies, since my student days in the 1980s. To this end, I trace a journey through the most outstanding milestones of feminist literary studies. The search for ways of reading literature that took into account women’s experiences and perspectives arose from the irritation of women professors and researchers like myself, who could not recognize themselves in the classical representations of what a woman is, wants and knows, because such images felt alien, even chimerical. That dissonance between one’s own experience and what hegemonic discourses have historically presented as the truth about women was the engine that drove me –and every feminist in the world– to seek the theoretical-methodological lenses necessary to reveal and resist the patriarchal bias that transforms sexual difference into political inequality.